2016
DOI: 10.1111/hae.13001
|View full text |Cite
|
Sign up to set email alerts
|

A world‐wide survey and field study in clinical haemostasis laboratories to evaluate FVIII:C activity assay variability of ADYNOVATE and OBIZUR in comparison with ADVATE

Abstract: Introduction: Discrepancies have been previously reported for one-stage clotting and chromogenic assays for FVIII activity analysis. Inter-laboratory variations in instruments, method of clot detection, assay set-up, reference standard calibration, reagent source and reagent composition all contribute to assay variability. Aim: To characterise multilaboratory assay variability in measuring ADYNOVATE, OBIZUR and ADVATE FVIII activity in human plasma and survey multinational FVIII activity assay preferences. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
91
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(102 citation statements)
references
References 31 publications
7
91
2
2
Order By: Relevance
“…The interlaboratory variability was similar for one‐stage and chromogenic assay results with CVs of 10%‐13% and 12%‐16%, respectively. There is usually an inverse relationship between the FVIII level and the inter laboratory CV for both one‐stage and chromogenic methods, that is, higher CVs at lower levels . In the present study, we observed interlaboratory CVs for samples containing Advate (10%‐12%) which were similar to the figures of 10%‐18% previously reported in several studies when FVIII activity levels were in the range of 35‐80‐IU/dL .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The interlaboratory variability was similar for one‐stage and chromogenic assay results with CVs of 10%‐13% and 12%‐16%, respectively. There is usually an inverse relationship between the FVIII level and the inter laboratory CV for both one‐stage and chromogenic methods, that is, higher CVs at lower levels . In the present study, we observed interlaboratory CVs for samples containing Advate (10%‐12%) which were similar to the figures of 10%‐18% previously reported in several studies when FVIII activity levels were in the range of 35‐80‐IU/dL .…”
Section: Discussionsupporting
confidence: 89%
“…Any laboratory assay that agrees with the assay used for potency assignment or recovers close to the target based on potency should therefore be clinically safe. Advate potency is assigned using a chromogenic assay in Europe or with a one‐stage assay in the United States . Advate used for both spiking and patient treatment samples was purchased in Europe with potency assignment by chromogenic assay.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… Two products (rFVIII Fc and rFVIII‐PEG) seemingly have no serious issues with any of the tested reagents; however, for both of these products, only field studies have been performed, with the aforementioned shortcomings . Of note, for rFVIII‐PEG, it was noted that silica reagents led to somewhat lower FVIII levels than ellagic acid/polyphenolic acid reagents; however, these differences were not quantified . Two other products (N8‐GP and BAY‐94‐9027) have discrepancies with regard to silica reagents, with correct measurement with SythaSIL and Pathromtin SL but decreased recoveries with STA‐PTT Automate and PTT‐SP . In addition, N8‐GP had discrepant results with ellagic acid reagents, with correct measurements with Actin FS and DG Synth but decreased results with SynthaFax .…”
Section: Factor VIII Concentrates and The Oscamentioning
confidence: 99%